2022
DOI: 10.1039/d1ta09015a
|View full text |Cite
|
Sign up to set email alerts
|

Structural rule of N-coordinated single-atom catalysts for electrochemical CO2 reduction

Abstract: Metal single-atom catalysts (SACs) on nitrogen-doped carbons exhibit an attractive prospect in catalysis. However, how to quickly collocate various metal centers with diversified N-coordination topologic structures to maximize the catalytic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 65 publications
(69 reference statements)
0
14
0
Order By: Relevance
“…7d). 189 The results demonstrated that TM SACs on GN 2 with the least N coordination achieved excellent CO 2 RR catalytic activity and selectivity.…”
Section: Optimization Strategy Of Sacsmentioning
confidence: 92%
“…7d). 189 The results demonstrated that TM SACs on GN 2 with the least N coordination achieved excellent CO 2 RR catalytic activity and selectivity.…”
Section: Optimization Strategy Of Sacsmentioning
confidence: 92%
“…Here, the cohesive energy (E c ) of metals, which only depends on the metal itself and can directly describe the binding strength of metal centers, is selected as the descriptor to assess the activity of catalysts for the NRR, which has been successfully used to understand the transition metal single-atom catalysts. 26 The detailed E c of transition metals are listed in Table S6. † 3.2.1 Activity trends.…”
Section: Evaluation Of Catalytic Performancementioning
confidence: 99%
“…That is to say, the stronger binding strength (i.e., more negative E c ) of active metal centers corresponds to the usually stronger adsorption of intermediates. 26 With these obtained relationships, we can then gain the free energy change (DG i , see calculation details in the table) of each elementary step of the NRR on the SAS, DAS and TAS, respectively. Accordingly, the curves of the limiting potential (U NRR ¼ ÀDG i(max) ) of the NRR on the SAS, DAS and TAS, that are oen used to evaluate the intrinsic activity of electrocatalysts, can be built up (Fig.…”
Section: Evaluation Of Catalytic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al realized low-temperature CO 2 methanation over CeO 2 -supported Ru single-atoms, with a turnover frequency of 7.41 × 10 −3 s −1 at 463 K. 16 Recently, transition metal single-atoms anchored on graphene and silicomolybdic were reported to show excellent CO 2 electroreduction activity. 17,18…”
Section: Introductionmentioning
confidence: 99%